Influence of VAC Therapy on Perfusion and Edema of Gracilis Flaps: Prospective Case-control Study. Issue 4 (28th April 2023) - Kuenlen, Anian; Waked, Karl; Eisenburger, Michael; Oramary, Alan; Alsherawi, Abeer; Ninkovic, Milomir
Abstract : Background: The gracilis muscle flap is a popular choice in reconstructive surgery to repair soft tissue defects or for functional restoration. Little is known on the influence of postoperative application of VAC (vacuum-assisted closure; Kinetic Concepts Inc., San Antonio, Tex.) therapy on perfusion and postoperative flap edema of free gracilis muscle flaps. Methods: In total, 26 patients with soft tissue defects of lower extremity underwent gracilis muscle flap reconstruction. The study group (VAC, n = 13) was supplied with postoperative negative pressure therapy as a dressing; the control group (NVAC, n = 13) was supplied with conventional fat gauze dressing. Postoperative measurements of micro- and macroperfusion were performed intraoperatively, on postoperative day (POD) 3 and POD 5. Flap edema measurement was performed intraoperatively, on POD 5 and 2 weeks after operation. Results: The VAC group showed significantly better macroflow during intraoperative VAC treatment, as well on POD 3 and POD 5. Venous outflow was also better with lower hemoglobin levels. Microflow was better in the NVAC group with higher measured oxygen levels. All gracilis muscle flaps of the VAC group showed significantly less flap edema compared with the control group. Conclusions: VAC application on free gracilis muscle flaps leads to significantly less postoperative flap edema, improved arterial macroflow, and improved venous outflow. VAC therapy can be used without any danger for patient's safety, as flap survival is not endangered, and presents an easy to handle and pleasant dressing regimen for nursing staff and patients.